(untitled) (Research, Society and Development, 2022)
Introduction: Breast cancer is caused by the disordered multiplication of breast cells, being the type of cancer that most affects the female audience. Objectives: to describe the knowledge of women about risk factors and screening programs for breast cancer and to present the screening methods used by them. Methodology: Cross-sectional, descriptive and qualitative-quantitative study involving 42 women over 40 years old who work at a Private University Center in Volta Redonda (RJ). An adapted questionnaire was used to identify breast cancer screening and detection actions. Results: the participants know the main risk factors for breast cancer; such as screening, they look for health units to perform mammography and clinical breast exams regularly, and they also perform self-palpation of the breasts with the purpose of self-knowledge of their body. and alerts to possible changes. Conclusion: Participants have good knowledge about risk factors and cancer screening methods, and undergo screening tests regularly.